Glasgow Aneurysm Score: a predictor of long-term mortality following endovascular repair of abdominal aortic aneurysm? - Anıl Özen (BMC, 2021)
Abstract Background To evaluate the value of Glasgow Aneurysm Score (GAS) in predicting long-term mortality and survival in patients who have undergone endovascular aortic aneurysm repair (EVAR) for abdominal aortic aneurysm (AAA). Methods A retrospective single-center study of 257 patients with non-ruptured AAA undergoing EVAR between January 2013 and 2021. GAS scores were compared between the survivors (group 1) and the long-term mortality (group 2) groups. Cox regression analysis was used to determine independent predictors of late mortality. Receiver operating characteristic curve (ROC) analysis was used to determine the optimum cut-off values of GAS values to determine the effect on late-mortality. Survival analysis was conducted using Kaplan-Meier. Results The study included 257 patients with a mean age of 69.75 ± 7.75 (46–92), who underwent EVAR due to AAA. Average follow up period was 18.98 ± 22.84 months (0–88). Fourty-five (17.8%) mortalities occured during long-term follow-up. A past medical history of cancer resulted in a 2.5 fold increase in risk of long-term mortality (OR: 2.52, 95% CI 1.10–5.76; p = 0.029). GAS values were higher in group 2 compared to group 1 (81.02 ± 10.33 vs. 73.73 ± 10.46; p < 0.001). The area under the ROC curve for GAS was 0.682 and the GAS cut-off value was 77.5 (specificity 64%, p < 0.001). The mortality rates in patients with GAS < 77.5 and GAS > 77.5 were: 12.8% and 24.8% respectively (p = 0.014). Every 10 point increase in GAS resulted in approximately a 2 fold increase in risk of long-term mortality (OR: 1.8, 95% CI 1.3–2.5; p < 0.001). Five year survival rates in patients with GAS < 77.5 and > 77.5 were 75.7% and 61.7%, respectively (p = 0.013). Conclusions The findings of our study suggests that an increase in GAS score may predict long-term mortality. In addition, the mortality rates in patients above the GAS cut-off value almost doubled compared to those below. Furthermore, the presence of a past history of cancer resulted in a 2.5 fold increase in long-term mortality risk. Addition of cancer to the GAS scoring system may be considered in future studies. Further studies are necessary to consolidate these findings.